Music, theater, and the moral treatment: the Casa dei Matti in Aversa and Palermo - Carmel Raz (Laboratoire Italien)
In the first half of the nineteenth century, the Casa dei Matti in Aversa and Palermo were renowned throughout Europe for using music to treat the insane. In an innovative approach to mental illness inspired by Pinel’s moral treatment, patients took regular part in theatrical productions, operas, and musical performances. This paper investigates the methods used at Aversa and Palermo in light of contemporary medical debates. I argue that the use of music and theater in these institutions should be understood not only within the context of the emerging field of psychiatry, but also as interacting with popular notions of the national characteristics of Italians. Relying on both historical accounts and fictional narratives, I end by considering how depictions of musical-theatrical treatment expressed the assumption that Italian minds and bodies had a special sensitivity to the arts.